Identifying and assessment the risk of material misstatement in control-based accounting system - СвятковскаяЕвгения Юрьевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2016)
Evgenia Yuryevna Svyatkovskaya - HSE. This paper analyzes the impact of the management the risk of material misstatement in accounting system for the internal control of financial transactions. The previous studies did not consider the management the risk of material misstatement as a component of accounting process. The research framework consists of several steps. First, the existing Russian research on models of accounting and internal control systems was investigated. Second, the Russian internal control legislative framework was analyzed. Lastly, internal control policies in Russian organizations were surveyed about the effectiveness of internal control to prevent the material misstatements. The research has shown the relationship between internal control, accounting and audit processes in organizations with effective internal control system based on the management of risk of material misstatement. Analysis of existing Russian internal legislative framework has shown inconsistent between the rules for building internal control system and their audit. The survey of internal control policies in Russian organizations has shown the weak of the build internal control systems to prevent the material misstatements.The integration of the identification and assessing risk of material misstatement in accounting process forms a new accounting model - control-based accounting system, which is treated as an accounting system designed to ensure the continuous control over every financial transaction. The risk mapping based approach was proposed for the identifying and the assessment the risk of material misstatement. The results of the research could be used for building a control-based accounting system and for the assessment the risk of material misstatement in this accounting system.